KEMAMPUAN MANAJERIAL KYAI DALAM MENGELOLA PONDOK PESANTREN AL-ITTIFAQ - Sri Widaningsih (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
The important management of Islamic boarding schools is very helpful in achieving educational goals in Islamic boarding schools. The purpose of this study is to describe and analyze the managerial abilities of Kyai in the process of managing Islamic boarding schools. This study uses a qualitative method with a "phenomenological naturalistic" approach adopted by Bogdan and Biklen (1982). This approach operationally places the researcher as the main instrument that visits data sources directly. Data were collected through observation, interviews, and documentation. The data is presented in the descriptive form and analyzed through inductive analysis by revealing the meaning of the observed conditions. The results of this study are based on findings in the field and references from existing theories, so almost 100% of the concepts that have been carried out by the Kyai in the process of managing Islamic boarding schools are almost the same as the existing theory, only a complete adjustment of existing management concepts and theories is needed. and is currently developing, and primarily must be supported by all components of education in Islamic boarding schools. The researcher recommends to all parties related to the world of education in general, especially education in Islamic boarding schools to be able to add insight into the concept of management in depth, especially regarding the concept of managerial ability in educational institutions/Islamic boarding schools, because management that is directed and systematically structured in the management process can help achieve goals